2012
DOI: 10.1523/jneurosci.5301-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Ecdysis Behavior inDrosophilaReveals Partially Overlapping Functions of Two Unrelated Neuropeptides

Abstract: Ecdysis behavior allows insects to shed their old exoskeleton at the end of every molt. It is controlled by a suite of interacting hormones and neuropeptides, and has served as a useful behavior for understanding how bioactive peptides regulate CNS function. Previous findings suggest that crustacean cardioactive peptide (CCAP) activates the ecdysis motor program; the hormone bursicon is believed to then act downstream of CCAP to inflate, pigment, and harden the exoskeleton of the next stage. However, the exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 43 publications
7
77
0
Order By: Relevance
“…This neuropeptide was discovered in the shore crab, Carcinus maenas, where it was shown to have a potent cardioacceleratory effect on semi-isolated heart preparations (Stangier et al, 1987). In insects, CCAP functions in ecdysis, hormone release and the contraction of visceral organs (Veelaert et al, 1997;Donini et al, 2001;Ewer and Reynolds, 2002;Sakai et al, 2004;Arakane et al, 2008;Lahr et al, 2012), and more relevant to the present study, CCAP is cardioacceleratory in both holometabolous and hemimetabolous insects (Furuya et al, 1993;Lehman et al, 1993;Wasielewski and The ampulla of an antennal APO propels hemolymph in the upward direction via an antennal vessel. When hemolymph reaches the distal end of the appendage, it is released into a wider antennal hemocoel and it flows in the downward direction as it returns to the head.…”
Section: Discussionmentioning
confidence: 73%
“…This neuropeptide was discovered in the shore crab, Carcinus maenas, where it was shown to have a potent cardioacceleratory effect on semi-isolated heart preparations (Stangier et al, 1987). In insects, CCAP functions in ecdysis, hormone release and the contraction of visceral organs (Veelaert et al, 1997;Donini et al, 2001;Ewer and Reynolds, 2002;Sakai et al, 2004;Arakane et al, 2008;Lahr et al, 2012), and more relevant to the present study, CCAP is cardioacceleratory in both holometabolous and hemimetabolous insects (Furuya et al, 1993;Lehman et al, 1993;Wasielewski and The ampulla of an antennal APO propels hemolymph in the upward direction via an antennal vessel. When hemolymph reaches the distal end of the appendage, it is released into a wider antennal hemocoel and it flows in the downward direction as it returns to the head.…”
Section: Discussionmentioning
confidence: 73%
“…Mouse GPCRs included a dopamine receptor (Drd1a) and an adenosine receptor (Adora2a) associated with human panic disorders (13). Honey bee GPCRs included CcapR and hormone receptor EthR, which are responsive to ecdysone (14,15) (Table S1). Fz2, a Wnt-activated receptor, was another GPCR identified in honey bee.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, global knockdown of rk in vivo using RNAi results in developmental arrest, rather than just impaired wing expansion, melanization and cuticle hardening (Loveall and Deitcher, 2010). A recent study also showed that deletion of the bursicon β-subunit results in significant lethality throughout pupariation, specifically during ecdysis (Lahr et al, 2012;Loveall and Deitcher, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…We subsequently used a series of Gal4 driver lines to target our tethered ligand to selected tissues and thus define the critical cell type(s) that requires rk and underlies the lethality/wing expansion phenotypes (Table 1). Although many studies have focused on the spatial and temporal release of bursicon (Lahr et al, 2012;Peabody et al, 2008;Peabody et al, 2009), the localization of the bursicon receptors that are essential for survival has remained elusive. Our study strongly supports that a peripheral rk, localized in muscle, plays an important role in Drosophila development.…”
Section: Research Articlementioning
confidence: 99%